Environmental and energy quality: sobane methodology adapted to canteens - Bellizzi, Yasmin (2020)
In the construction market, particularly in the maintenance and rehabilitation segment, users’ input is not often considered before selecting any refurbishment procedures to improve indoor comfort. The objective of this work is to present a methodology to evaluate the indoor environmental and energy quality in canteen buildings, and suggest indoor rehabilitation measures in a more efficient way, through the perspective of the user. The risk management strategy SOBANE – Screening, Observation, Analysis and Expertise was used as a reference to develop the methodology for canteens. Each one of the four levels, and its tools, were adapted to suit the object of the study. The first two levels – Screening and Observation – were tested in the canteen of the Polytechnic Institute of Bragança – IPB. First level results revealed that the building needs to be refurbished. The second level results obtained from a questionnaire revealed that the respondents found the indoor confort in the canteen as: an indoor environment without air-flow (63%); with stuffy air (61%); a clean space (75%); high temperature (63%) and noisy (80%). Additionally, a comparison was made between the actual and estimated energy consumption profiles for the verification of parasitic load consumption. The results show that estimated and monitored energy consumption profiles have similar behaviors.